(untitled) (Journal of Medicine, 2021)
Background: Snakebite is a neglected public health problem in many countries of the world. Being a tropical country Bangladesh is also facing this problem. In this case series we have tried to focus the illiteracy, prejudice and mismanagement happen in snake bite cases from primary to tertiary level and how effective management can save life of snake bite victim. Case presentation: Among the 29 snake bite cases admitted in a medicine ward of tertiary care hospital four were venomous bites- two male and two female. Our patients came from around Dhaka city. Though victim failed to bring the snake, by studying clinical features and syndromic approaches we suspected Kraits as the culprit in three cases and Cobra in one case. Time period between bite and attend to hospital ranged from 4 hr to 16.30 hours. All victims had inappropriate application of tourniquet to their limbs as a first aid management. Most of them first visit OZHA (traditional healer). Two of them developed respiratory failure. All cases were managed in ICU with polyvalent ASV. One developed anaphylaxis which was managed with adrenaline. All patients recovered completely. Conclusion: Arrival to hospital without delay, facilities for management with trained physicians and proper supply of ASV may reduce death from snake bite and reduce financial burden to the patient. Developing public awareness to remove prejudice about snakes and identifying venomous snake bite is also necessary. J MEDICINE JAN 2021; 22 (1) : 72-76